The response of intravitreal bevacizumab injection at a child with proliferative diabetic retinopathy and DIDMOAD syndrome - Turgut, Burak; Can, Nagehan Bilir; Çeliker, Ülkü; Demir, Tamer (My University, 2013)
DIDMOAD Syndrome (Wolfram Syndrome) is presented with diabetes insipidus, diabetes mellitus, optic atrophy, and deafness at childhood. We evaluated the anatomic and functional responses after bilateral intravitreal injection of bevacizumab for a pediatric patient with DIDMOAD Syndrome and proliferative diabetic retinopathy at follow-up in our clinic. Especially, in the patients with vitreous hemorrhage and/or child cases which panretinal laser photocoagulation can not be completed or performed, intravitreal bevacizumab injection can be performed as an effective and safe treatment.
Proliferatif diyabetik retinopatisi olan DIDMOAD sendromlu bir çocukta intravitreal bevacizumab enjeksiyonuna yanit
Keywords: Bevacizumab; Panretinal laser photocoagulation; Proliferative diabetic retinopathy